2013
DOI: 10.1017/s0959774313000486
|View full text |Cite
|
Sign up to set email alerts
|

The Life of Things Long Dead: a Biography of Iron Age Animal Skulls from Battlesbury Bowl, Wiltshire

Abstract: This study expands perceptions of ritual behaviour in the British Iron Age, which conventionally focus on the deposition and burial of objects. Classification of animal bones as special deposits in Iron Age Britain, and interpretation of the ritual activities they may represent, has tended to concentrate on the significance of their burial location and composition and/or the cultural perception of the particular animal species deposited. Other than for consumption and sacrifice, little consideration has been g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It is hard to avoid placing more focus on the human skull fragments found in the cultural layers than the animal skull fragments found in similar circumstances, particularly as the former often are singled out in field reports and feature in the overall interpretation of the sites, while the latter are most often mentioned only alongside other animal bone fragments in an osteological analysis. There are also generally more animal skull fragments found in cultural layers than human skull fragments, and as such any credible argument of special deposition of animal remains is predicated upon a close consideration of taphonomic factors, associated finds and otherwise identifiable patterns (see also Hambleton 2013).…”
Section: Human and Animal Skull Deposits And Selective Treatmentmentioning
confidence: 99%
“…It is hard to avoid placing more focus on the human skull fragments found in the cultural layers than the animal skull fragments found in similar circumstances, particularly as the former often are singled out in field reports and feature in the overall interpretation of the sites, while the latter are most often mentioned only alongside other animal bone fragments in an osteological analysis. There are also generally more animal skull fragments found in cultural layers than human skull fragments, and as such any credible argument of special deposition of animal remains is predicated upon a close consideration of taphonomic factors, associated finds and otherwise identifiable patterns (see also Hambleton 2013).…”
Section: Human and Animal Skull Deposits And Selective Treatmentmentioning
confidence: 99%
“…Complex treatment of the horse skull after the death of the animal but prior to the deposition of its remains has also been identified in some areas. Archaeological evidence from Battlesbury Bowl, Wiltshire demonstrates the careful and selective deposition of some horse and cattle skulls (Hambleton 2013). The taphonomic wear on many of the skulls indicated that they had been cleaned some time prior to deposition, perhaps suggesting that they had been hung on walls or posts for a duration (Hambleton 2013, 490).…”
Section: One Example From the Upper Thames Valley Is At The Hillfort mentioning
confidence: 99%
“…The Battlesbury horse skulls also demonstrate an emphasis on male animals (Hambleton 2013, 490). Horses are not the only animals to undergo special treatment across Iron Age Britain (Hambleton 2013;Madgwick 2010), and it should be noted that such specialised treatment of animal remains is not limited to those animals depicted on late, pre-Roman Iron Age coinage. However, cross cultural practices involving the display of horse heads and skins has been noted by Wilson (1999), and could go some way to explaining possible post-mortem treatment of faunal remains.…”
Section: One Example From the Upper Thames Valley Is At The Hillfort mentioning
confidence: 99%
“…Zooarchaeologists and material culture specialists focusing on British prehistory are also now approaching animals, humans and objects as cohabiting as significant others (Brittain & Overton 2013). In this sense, the social role of animals and faunal remains becomes the focus (Hambleton 2013; Madgwick 2008; 2010; Overton & Hamilakis 2013), thus viewing the faunal remains more as a form of material culture that has meaning and cultural significance over time (Gosden & Marshall 1999; Kopytoff 1986). There is a strong argument for coins to be approached from a similar stance (Kemmers & Nanouschka 2011).…”
Section: Coins As Affective Objectsmentioning
confidence: 99%